Penerapan Strategi Digital Marketing dalam Meningkatkan Penjualan Tahu Susu Antapani Cabang Galuh Mas di Karawang - Aryani, Windy; Retnosary, Rieke; Yani, Dini (MES Bogor, 2024)
This research on the Antapani Milk Tofu business aims to analyze and provide an explanation of the use of digital marketing on the impact of increasing income in the Antapani milk tofu business, Galuh Mas branch in Karawang. This case study was designed using a qualitative descriptive approach. The locus of this research is Antapani Milk Tofu which is located on Jl. Bharata Raya, Galuh Mas-Karawang, West Java. The descriptive method is used to describe the efforts of the owners and employees of Tahu Susu Antapani in developing its marketing through digital marketing. This research collects data through interviews, observation, documentation, the internet and journals and articles. By conducting direct interviews with employees, in this observation, researchers obtained data when observing social media accounts. The results of interviews and studies show the positive effects of using digital marketing with social media and e-commerce platforms which have increased the income of Antapani Milk Tofu, Galuh Mas Branch. By utilizing social media, promoting Antapani milk tofu products becomes easy; without promotion, it will be difficult to sell the product. With a digital marketing strategy using social media to promote Antapani milk tofu, it is better known by the people of Karawang, and the sales income obtained increases. From several interviews with consumers, they also found out about the Antapani milk tofu product from the media. social.